Dampak Revitalisasi Kota Lama Semarang sebagai Destinasi Wisata Heritage : Perspektif Kebijakan Konservasi - Alifah Nadine Griselda; Teguh Yuwono (Journal of Politic and Government Studies, 2026)
The revitalization of Semarang's Old Town as a heritage tourism destination faces a dilemma between preserving Dutch colonial cultural heritage with its authentic Nieuwe Bouwen and Indo-European architecture and economic development amidst massive urbanization and environmental threats such as tidal flooding and land subsidence, as stipulated in Law No. 11/2010 concerning Cultural Heritage and Semarang City Regulation No. 2/2020. This research focuses on Semarang's Old Town compared to Jakarta's Old Town due to its unique context as a strategic port city in Central Java that has experienced more severe physical degradation, poor drainage infrastructure, and the urgency of recent revitalization through the Old Town Site Management Agency (BPSKL). This contrasts with Jakarta's Old Town, which has been established as a UNESCO World Heritage site with a long-standing commercial tourism presence. The research's appeal lies in the analysis of conservation policy implementation using the Edward III model (communication, resources, disposition, bureaucratic structure), a qualitative descriptive methodology with in-depth interviews with the Department of Culture and Tourism, BPSKL, and business actors, participatory observation, and triangulation of secondary data from urban heritage revitalization reports. The results of the study indicate that the implementation of conservation policies has been quite successful with coordinated communication between stakeholders, although hampered by budget constraints, cross-agency bureaucratic coordination, and low awareness of the local community. Revitalization has succeeded in increasing tourist visits by 20-30% per year, encouraging the creative economy through the adaptive reuse of heritage buildings into art cafes, galleries, and cultural workshops, but has also given rise to negative impacts in the form of gentrification that displaces traditional traders, overtourism on weekends, and the risk of erosion of architectural authenticity due to excessive commercial modifications. The conclusion recommends strengthening the role of BPSKL and DISBUDPAR through fiscal incentives for sustainable adaptive reuse, inclusive multi-stakeholder participation, and a monitoring system based on UNESCO's Outstanding Universal Value (OUV) to achieve an optimal balance between historical preservation and long-term economic benefits.